The Effect of TROP2 Expression on Papillary Thyroid Carcinoma Development in Iraqi Patients (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background : Papillary Thyroid Carcinoma (PTC) is common type of the thyroid cancers, it’s onset in female at 30-50 years more than male and account for about 80% of all thyroid cancer cases . PTC diagnosis depend on histo-pathological finds of abnormal papillary architectures in the tissue as golden standerd of PTC diagnosis . Trophoblast cell surface antigen 2 (TROP2) is trans-membrane glycoprotein receptor ,encoded by Tacstd2 gene , observe in various cancer types specially epithelial cancers . TROP2 has the up-regulation ( overexpression) in cancer cells such as pancreatic , thyroid and ovarian cancers. Objective of the Study:It’s shown up-regulation of TROP 2 in PTC Iraqi patients by Immunohistochemical method.Materials and Methods: The current study done in Al-Yarmook Teaching Hospital from March 2020 to January 2021 , was included 30 cases of PTC patients and 30 healthy subjects , all of subject’s age were more than 30 years . This study depend on collect of paraffin embedded PTC biopsies then used Immunohistochemical method to examined the present of TROP2 in all cases.Results: This qualitative study shows significant expression of TROP2 in PTC patients compare with control groups .Conclusion: The current study demonstrate effect of TROP2 expression on PTC development
Keywords: Papillary Thyroid Carcinoma(PTC), TROP2 and Immunohistochemical.